Analysis of the Influence of Religiosity, Loyalty and Murabahah Margin on Interest in Murabahah Contract Financing at BMT Mass - Akbar, Abu Bakar (International Journal of Seocology, 2023)
This research aims to determine the influence of religiosity, loyalty and murabahah margin on interest in financing murabahah contracts at BMT Mass. This research uses a quantitative approach with a population of BMT Mass members or customers who have murabahah financing, a sample of 61 was taken using the Slovin formula and the sampling technique used random sampling. Data analysis uses multiple linear regression models. The results of this research partially show that the religiosity variable has a significant effect on interest in financing but does not have a positive effect on interest in financing. The loyalty variable does not have a significant effect on interest in financing but has a positive effect on interest in financing. The murabahah margin variable does not have a significant effect on interest in financing but has a positive effect on interest in financing. Meanwhile, religiosity, loyalty and murabahah margin can simultaneously influence 60.7% of interest in financing murabahah contracts at BMT Mass.